Theoretical study of the optical properties of the noble metal nanoparticles: CD and MCD spectroscopy - Karimova, Natalia Vladimirovna (Kansas State University, 2017)
Gold and silver particles with dimensions less than a nanometer possess unique characteristics and properties that are different from the properties of the bulk. They demonstrate a non–zero HOMO–LUMO gap that can reach up to 3.0 eV. These differences arise from size quantization effects in the metal core due to the small number of atoms. These nanoparticles have attracted great interest for decades both in fundamental and applied research. Small gold clusters protected by various types of ligands are of interest because ligands allow obtaining gold nanoclusters with given sizes, shapes and properties. Three main families of organic ligands are usually used for stabilization of gold nanoclusters: phosphine ligands, thiolate ligands and DNA. Usually, optical properties of these NPs are studied using optical absorption spectroscopy. Unfortunately, sometimes this type of spectrum is poorly resolved and tends to appear very similar for different complexes. In these cases, circular dichroism (CD) and magnetic circular dichroism (MCD) spectroscopy can be applied. However, the interpretation of experimental CD and MCD spectra is a complicated process. In this thesis, theoretically simulated CD and MCD spectra were combined with optical absorption spectra to study optical activity for octa– and nona– and undecanuclear gold clusters protected by mono– and bidentate phosphine ligands. Additionally, optical properties of bare and DNA protected silver NPs were studied. Theoretical CD spectra were examined to learn more about the origin of chirality in chiral organometallic complexes, and to contribute to the understanding of the difference in chiroptical activity of gold clusters stabilized by different phosphine ligands and DNA–stabilized silver clusters. Furthermore, optical properties of the small centered gold clusters Au₈(PPh₃)₈²⁺ and Au₉(PPh₃)₈³⁺ were examined by optical absorption and MCD spectra using TDDFT. Theoretical MCD spectra were also used to identify the plasmonic behavior of silver nanoparticles. These results showed that CD and MCD spectroscopy yield more detailed information about optical properties and electronic structure of the different chemical systems than optical absorption spectroscopy alone. Theoretical simulation of the CD and MCD spectra together with optical absorption spectra can be used to assist in the understanding of empirically measured CD and MCD and provide useful information about optical properties and electronic structure.
Keywords: Time-dependent density functional theory; Optical properties; Gold nanoparticles; Silver nanoparticles; Chirality; Localized surface plasmon